'All of that's gone now': The failure to sustain police-youth programmes in Baltimore City. (June 2018) - Caldas, Stephanie V; Turkel, Rachel; Nelson, Allyson; Pandey, Shristi; Wu, Yumeng; Broaddus, Elena; Beebe, Madeleine; Rivera, Gia; Winch, Peter
Extra-curricular programmes that unite police officers and youth (hereafter: 'police-youth programmes') have long been recommended to ameliorate the often-strained relationship between these groups. Baltimore's history of police-youth programming includes initiating and discontinuing a variety of programmes. Researchers conducted in-depth interviews and focus group discussions among diverse stakeholders to identify barriers to sustaining police-youth programmes. Stakeholders described lack of political will, conflicting policing philosophies, and negative police-community dynamics. Participants were optimistic about the potential impact of quality programming, despite these barriers. Police-youth programmes have the capacity to improve police-youth relationships in Baltimore. Strategies to ensure sustainability and increase impact are discussed.